Pelanggaran Kode Etik Guru Dalam Pengelolaan Dana Tabungan Siswa Di Pangabdaran:Studi Kasus Dan Implikasi - Dina Anggita; Gladys Chintia; Inggit Haryanti; Nisa Sweet Sinaga (GLOBAL SCIENTS PUBLISHER, 2025)
The case of ethical violations by teachers in the return of student savings funds in Pangandaran has caused financial losses and decreased public trust in the teaching profession. This study employs a qualitative case study method to analyze the impact of these violations on the quality of education and the image of teachers, while also identifying appropriate solutions. The findings highlight the need for increased supervision, transparency in fund management, professional ethics training, and strict enforcement of sanctions to restore teacher integrity and maintain the culture of saving as part of character education. This study contributes significantly to strengthening educational policies and teacher professional ethics in Indonesia.